2008
DOI: 10.1103/physrevd.78.123007
|View full text |Cite
|
Sign up to set email alerts
|

Viscous damping ofr-mode oscillations in compact stars with quark matter

Abstract: We determine characteristic timescales for the viscous damping of r-mode oscillations in rapidly rotating compact stars that contain quark matter. We present results for the color-flavor-locked (CFL) phase of dense quark matter, in which the up, down and strange quarks are gapped, as well as the normal (ungapped) quark phase. While the ungapped quark phase supports a temperature window 10 8 K ≤ T ≤ 5 × 10 9 K where the r-mode is damped even for rapid rotation, the r-mode in a rapidly rotating pure CFL star is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 88 publications
2
73
0
Order By: Relevance
“…[33] found that the strangelet crystal crust did not have the right spectrum of toroidal shear modes to account for current observations: it would be interesting to see whether taking in to account the surface tension and Debye screening affects that conclusion. Other aspects of the phenomenology of the crust could also be studied, for example (a) the thermal response of the crust to accretion [35]; (b) the role of the crust in the trapping of neutrinos and photons just after a type-II supernova [36]; (c) the spectrum of photons radiated from the surface of a quark star [37,38,39]; (d) the contribution of the crust to the moment of inertia and glitches [40]; (e) the damping of r-modes in by shear viscosity in the crust [41,42] (for quark stars, the contribution from the interior has been calculated [43,44]); (f) the thermal relaxation time of the crust and its response to the postsupernova "cooling wave" [45]. The thermal relaxation time of the crust depends on the thermal conductivity, for which we can make a very rough estimate using appendix A of Ref.…”
Section: Discussionmentioning
confidence: 99%
“…[33] found that the strangelet crystal crust did not have the right spectrum of toroidal shear modes to account for current observations: it would be interesting to see whether taking in to account the surface tension and Debye screening affects that conclusion. Other aspects of the phenomenology of the crust could also be studied, for example (a) the thermal response of the crust to accretion [35]; (b) the role of the crust in the trapping of neutrinos and photons just after a type-II supernova [36]; (c) the spectrum of photons radiated from the surface of a quark star [37,38,39]; (d) the contribution of the crust to the moment of inertia and glitches [40]; (e) the damping of r-modes in by shear viscosity in the crust [41,42] (for quark stars, the contribution from the interior has been calculated [43,44]); (f) the thermal relaxation time of the crust and its response to the postsupernova "cooling wave" [45]. The thermal relaxation time of the crust depends on the thermal conductivity, for which we can make a very rough estimate using appendix A of Ref.…”
Section: Discussionmentioning
confidence: 99%
“…3, which is taken from Ref. [41]. We see that the forbidden region for various models of nuclear matter (left panel) is quite different from that for models of hybrid stars (right panel).…”
Section: R-mode Spindownmentioning
confidence: 94%
“…Using Eqs. (7), (8), (28), and (29), we find that the real part of the viscosities can be expressed as…”
Section: A Analytical Resultsmentioning
confidence: 96%
“…(7), (8), (28), and (29), one can find the real part of the viscosities. In this case we find that the frequency dependence of the coefficients is different from the case where only the kaons (or phonons) are considered.…”
Section: A Analytical Resultsmentioning
confidence: 99%